Poetic Inquiry Coming of Age: A Review of "Poetry, Poetic Inquiry and Rwanda: Engaging with the Lives of Others" by Laura Apol - Sullivan, Anne McCrary (Art/Research International, 2022)
Laura Apol’s Poetry, Poetic Inquiry and Rwanda: Engaging with the Lives of Others (2021) traces the author’s long relationship with survivors of the 1994 Rwanda holocaust in which thousands of Tutsi were murdered by their neighbors, and examines the ways in which her personal uses of poetry for coping with painful subject matter became a longitudinal poetic inquiry. This review responds to themes of relational poetic inquiry and the development of poetic craft and suggests that the author’s development reflects the development of the field of poetic inquiry and marks a stage of accomplishment.